TAX AMNESTY : SEBUAH HARAPAN TERHADAP CAPITAL INFLOW - Nanik Sisharini (Jurnal Manajemen dan Kewirausahaan, 2016)
Taxation policy reforms has been done by the government with the issuance of Law No. 11 year 2016 about Tax Amnesty. The background of the issuance of this law : a) there is still treasure the community both in the country and foreign who have not yet fully reported in the Annual Tax Income, b) to increase state revenues and economic growth as well as awareness and compliance community in the implementation of tax obligations . Although the government wants tax amnesty to secure tax revenue, but in general they wants it for the repatriation of capital. The goal is to increase the liquidity is getting tighter, so eventually bank deposits can be cheaper, bank lending rates fell and investment will increase. In addition, the quality of economic growth will increase by decreasing of unemployment, inequality, and poverty. To obtain a Tax Amnesty, the tax payer must disclose truthfully how the property owned which have not paid or partially paid taxes in the Letter of Statement and pay the ransom that provisions stipulated in the Act, and not subject to administrative sanctions taxation and criminal sanctions in the area of taxation. The ransom money to be paid in full to the state treasury through the Bank Perception (Bank elected to hold funds Tax Amnesty). Institution Tax Amnesty container fund is 19 Banks, 19 securities firms, and 18 of the Investment Manager. Tax payers who intend to bring funds owned to Indonesian territory, at least to invest of 3 years commencing from the funds transferred by the tax payer to the Special Account through the Bank Perception. Investment instruments include in the form of government securities of the Republic of Indonesia, the bonds of State BUMN, bond financing institution owned by the government, financial investments in the Bank's perception, bonds private companies whose trade is supervised by the Financial Services Authority, infrastructure investment through government cooperation with corporate, investment real sector based on the priorities set by the Government; and/or other forms of investment constituted under the provisions of the legislation.